Diversity of partial sequence leptin gene (Exon 3) in crossbred cattle compared to GenBank database - DEVI ERMAWATI; PANJONO PANJONO; SIGIT BINTARA; TETY HARTATIK (Society for Indonesian Biodiversity, 2022)
Abstract. Ermawati D, Panjono, Bintara S, Hartatik T. 2022. Diversity of partial sequence leptin gene (Exon 3) in crossbred cattle compared to GenBank database. Biodiversitas 23: 5614-5620. Genetic marker method that is often used to select cattle is Single Polymorphism Nucleotide (SNP). Single Polymorphisms Nucleotide (SNP) has been found in various candidate genes, one of which is the leptin gene. Leptin is a gene that affects reproduction and cattle weight. Therefore, this research aims to identify SNP of the leptin gene (exon 3) in Crossbred cattle by comparison with GenBank data. A sample of Crossbred cattle was taken from Klaten in Central Java, Indonesia. Afterward, DNA sequencing results were analyzed with BioEdit to identify SNP. BioEdit software was used for DNA sequencing alignment part of intron 2, exon 3 and 3'UTR. The MEGA 11.1.1 program was used to analyze and edit the genetic distance and phylogenetic tree based on the SNP leptin gene. The result shows that nine variations of SNPs were found in exon 3. The phylogenetic tree shows that the Crossbred cattle, Bos taurus, Bos indicus, Hereford, Friesian Holstein and Bali, were in the same cluster. HindIII restriction enzyme can be recommended for genotyping Crossbred cattle using PCR RFLP. This research provides information on SNP in the leptin gene so that it can be used for further research on the association of the leptin gene to growth and reproduction.